Geoprocessamento aplicado ao monitoramento dos índices de criminalidade no agreste meridional de Pernambuco - Melo, Felippe Pessoa de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The Southern Agreste Pernambuco comprises eighteen cities. Among them are Garanhuns and Lajedo that occupy a prominent position in relation to the high rates of intentional lethal violent crimes (ILVC). By using the geographic information system (GIS) ArcGIS, in line with the vector data from the Brazilian Institute of Geography and Statistics (IBGE), and the information from the United Nations Development Program (UNDP), a geographic database was made, allowing interpolation, analysis, interpretation of information and preparation of thematic maps required to spatialize this geographical dynamics.